2022
DOI: 10.1371/journal.pone.0272425
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of Staphylococcus aureus isolates causing osteoarticular infections in otherwise healthy children

Abstract: Background Pediatric osteoarticular infections are commonly caused by Staphylococcus aureus. The contribution of S. aureus genomic variability to pathogenesis of these infections is poorly described. Methods We prospectively enrolled 47 children over 3 1/2 years from whom S. aureus was isolated on culture—12 uninfected with skin colonization, 16 with skin abscesses, 19 with osteoarticular infections (four with septic arthritis, three with acute osteomyelitis, six with acute osteomyelitis and septic arthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Newer technologies like novel antibiotic laden biomaterials are made available with a view to reducing this complication. Further additions to the armamentarium aiming at reduction of recurrence include: use of artificial intelligence for diagnostics, 20 predictive modelling for risk factors, 21 genomic characterisation for virulence and antibiotic resistance, 22 novel 3D printed customised implants 23 and aggressive, and combined osteo-plastic surgical strategies. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Newer technologies like novel antibiotic laden biomaterials are made available with a view to reducing this complication. Further additions to the armamentarium aiming at reduction of recurrence include: use of artificial intelligence for diagnostics, 20 predictive modelling for risk factors, 21 genomic characterisation for virulence and antibiotic resistance, 22 novel 3D printed customised implants 23 and aggressive, and combined osteo-plastic surgical strategies. 24 …”
Section: Discussionmentioning
confidence: 99%
“…AHOM can cause devastating destruction of the bone due to tissue necrosis, leading to late sequelae like chronic osteomyelitis (1.7%) 3 and pathological fractures 5,23,31,36 (Figure 6). Complications such as these are more common in children in LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4]7,12,[16][17][18] Some studies have reported a higher median age of presentation of between 6.7 and 11.1 years. 5,8,14,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Males appear to be between 1.2 and 3.6 times more affected than females.…”
Section: Epidemiologymentioning
confidence: 97%
See 1 more Smart Citation